Review of SIP based DoS attacks - Jama, Abdirisaq M.; Khalifa, Othman Omran (ATS (Association of Technology and Science, India), 2016)
The Voice over Internet Protocol (VoIP). The VoIP is relatively new and is gaining more and more popularity as it offers a wide range of features and is much more cost effective as compared to the traditional PSTN. But the VoIP brings with it certain security threats which need to be resolved in order to make it a more reliable source of communication. Session Initiation Protocol (SIP) today is considered the standard protocol for multimedia signaling, and the result is a very generic protocol. SIP is specified by the IETF in RFC 3261. From a structural and functional perspective, SIP is application layer signaling text-based protocol used for creating, modifying, and terminating multimedia communications sessions among Internet endpoints. Unfortunately, SIP-based application services can suffer from various security threats as Denial of Service (DoS). attacks on a SIP based VoIP infrastructure that can severely compromise its reliability. In contrast, little work is done to analyze the robustness and reliability of SIP severs under DoS attacks. In this survey, we are discussing the DoS flooding attack on SIP server. Firstly, we present a brief overview about the SIP protocol. Then, security attacks related to SIP protocol. After that, detection techniques of SIP flooding attack and various exploited resources due to attack were discussed and finally the paper reviews previous work done on SIP based DoS attacks